UNDERSTANDING THE STATE BUILDING OF MOUNTED PASTORAL NOMADS ON SEDENTATION AND MERCANTILE ACTIVITY OF KHAZAR KHANATE AND VOLGA BULGARS - C. Şimşek (Әл-Фараби Атындағы Қазақ Ұлттық Университеті хабаршы шығыстану сериясы, 2022)
The mounted pastoral nomadism was the dominant socio-economical system in Desht-i Kipchak steppes for thousands of years. However, the state building methods and effectiveness of state building apparatus of mounted pastoral nomadic people were subject of debate for researchers. The commerce and sedentation were two important factors in understanding the debatable subjects of this sedantation processes of mounted pastoral nomads. Khazar Khanate and Volga Bulgars were taken as foundations of this study for analyzing and these two factors; sedentation and commerce. After giving very brief historical background about mounted pastoral nomads, Khazar Khanate and Volga Bulgars, this study focuses on describing mercantile activity of these two states as well as their roles transcontinental trade roads. The Islamic sources and material findings are taken into consideration while describing the relation between commercial activity and state building process of Khazar Khanates and Volga Bulgars. Finally, the study concludes the research on the efficiency of commercial activity, and how this efficiency determined the state building as well as sedentation of mounted pastoral nomads. Key words: Mounted Pastoral Nomads, Sedentation, State building, Commerce